Deep Vein Thrombosis: A Rare Association with Tuberculosis. (Journal of Medicine, 2012)
We are reporting two cases of bilateral extensive lower leg deep vein thrombosis in young male patients without any risk factors. First case was diagnosed as left sided tuberculous pleural effusion and second case was sputum smear positive pulmonary tuberculosis. In both patients, deep vein thrombosis developed during first month of treatment and inguinal pain was the first symptom. The second case had an attack of pulmonary thromboembolism. The cause effect relationship between deep vein thrombosis and tuberculosis or anti-tubercular drug (particularly rifampicin) has been discussed as such association may have significant therapeutic implications.DOI: http://dx.doi.org/10.3329/jom.v13i1.8843 JOM 2012; 13(1): 106-108